Evaluasi Trichoderma dalam Mengendalikan Penyakit Rebah Kecambah Tanaman Cabai - Ahmad Muslim; Komar Palimanan; Harman Hamidson; Abdullah Salim; Nirwati Anwar (Jurnal Fitopatologi Indonesia, 2014)
Damping-off disease is commonly occurred in chili pepper field and always caused significant effect on chili production. This experiment was conducted to determine the ability of 14 isolates of Trichoderma isolated from lowland swampy area in South Sumatera against damping-off disease. The result showed that treatment of Trichoderma significantly inhibited damping-off disease caused by Rhizoctonia solani. Treatment of Trichoderma effectively reduced the percentage of pre-emergence damping-off, post-emergence damping-off, and disease severity by 51.8–100%, 80–100%, and 51.90–96.96%, respectively. The treatment was also capable to increase percentage of height and fresh weight of chili pepper seedling, i.e. 45.45–64.37% and 37.78–81.19%, respectively.